A comparative study between single antibiotic prophylaxis and double antibiotic prophylaxis for reduction in incidence of surgical site infection in patients undergoing mesh hernioplasty - Garg, Navneet; Joshi, Bipin; Sharma, Prayag; B. Krishnasagar, Mrunal (International Surgery Journal, 2025)
Background: This study aims to evaluate and compare the effect of single antibiotic prophylaxis and double antibiotic prophylaxis for reducing incidence of surgical site infection (SSI) in patients undergoing mesh hernioplasty. Methods: It is a prospective study conducted at general surgery inpatient department, Rama medical college hospital and research centre, Hapur, U.P. from December 2022-March 2024. Intervention was surgery mesh hernioplasty. Injection ceftriaxone 1 gm (third generation cephalosporin) in single antibiotic group and injection ceftriaxone 1 gm (third generation cephalosporin) + injection amikacin 500 mg (Aminoglycoside) in double antibiotic group were given. Patients of either gender between 14-80 years of age with primary, unilateral or bilateral inguinal hernia, femoral hernia, umbilical hernia, ventral hernia or incisional hernia who are planned to undergo mesh hernioplasty were included and patients with diabetes mellitus, on steroid therapy, cigarette smokers, immunocompromised status like HIV, malignancy and abnormal KFT/RFT were excluded. Single and double antibiotic group were divided. Results: The incidence of SSI in both groups was noted. The incidence of SSI in single antibiotic group (28%) was higher than the incidence of SSI in double antibiotic group (12%). No patient underwent mesh removal and no significant difference in terms of post-operative complications was observed in the results of both groups. Conclusions: Double antibiotic prophylaxis was more effective than single antibiotic prophylaxis in decreasing the incidence of SSI in patients who undergo mesh hernioplasty by 16% as per the study.